2015
DOI: 10.1210/jc.2015-2649
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Differences in Hepatic Fat Oxidation and Synthesis May Explain the Higher Propensity for NAFLD in Men

Abstract: The combination of lower dietary FA oxidation and a prolonged increase in DNL observed in men may represent partitioning of FA into esterification and storage pathways within the liver, leading to greater VLDL-TG production, and predispose to the sex difference in hepatic steatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
119
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(135 citation statements)
references
References 46 publications
12
119
2
2
Order By: Relevance
“…In humans, men have a higher rate of hepatic steatosis than women 38 . However, sex differences in offspring of obese pregnancies in animal models are less clear, with some studies showing increased liver triglyceride content in male offspring 39 , female offspring 40 , or no differences between sexes 29 .…”
Section: Developmental Programming Of Nafldmentioning
confidence: 99%
“…In humans, men have a higher rate of hepatic steatosis than women 38 . However, sex differences in offspring of obese pregnancies in animal models are less clear, with some studies showing increased liver triglyceride content in male offspring 39 , female offspring 40 , or no differences between sexes 29 .…”
Section: Developmental Programming Of Nafldmentioning
confidence: 99%
“…The study was approved by Portsmouth Clinical Research Ethics Committee, and all subjects gave written informed consent. Data from a portion of the subjects reported in this work were obtained as part of another previously published study (19).…”
Section: Participants and Protocolmentioning
confidence: 99%
“…The evening before the study day, subjects consumed deuterated water ( 2 H 2 O) (3 g/kg body water) and continued to consume 2 H 2 O during the course of the study day for the measurement of fasting and postprandial hepatic DNL (19 (19), and at 360 min were given a glucose drink (75 g glucose) to assess the second meal effect (22). Repeated blood and breath samples were taken during the study period.…”
Section: Metabolic Study Daymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, both epidemiological data and animal studies have shown significant sex-specific differences in the prevalence of NAFLD [1720]. Before the age of 50, men have an increased risk of developing severe NAFLD.…”
Section: Introductionmentioning
confidence: 99%